2018
DOI: 10.1177/0300060518781476
|View full text |Cite
|
Sign up to set email alerts
|

Does narrative medicine education improve nursing students’ empathic abilities and academic achievement? A randomised controlled trial

Abstract: ObjectiveTo determine the effectiveness of a narrative medicine educational intervention on the empathic abilities and academic achievement of Chinese nursing students.MethodsA cluster randomised controlled trial was conducted between January 2015 and July 2017. Six class clusters (two controls, four interventions) comprising 180 nursing students were included in this trial. After pre-tests to obtain baseline measurements, two control classes (Group 1) attended regular medical education courses, two interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 38 publications
4
33
0
9
Order By: Relevance
“…These findings are in agreement with the study of Heidke et al,37 which revealed that incorporation of recorded health-care consumers’ interviews in a first-year nursing course significantly improved empathy in students. In line with recent studies highlighting the efficacy of experiential learning in empathy-competence acquisition,27,30,4650 our results indicate moderate levels of empathy among nursing students at baseline, which had significantly improved, after intervention, as noted by other similar studies 23,41,46,4951…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with the study of Heidke et al,37 which revealed that incorporation of recorded health-care consumers’ interviews in a first-year nursing course significantly improved empathy in students. In line with recent studies highlighting the efficacy of experiential learning in empathy-competence acquisition,27,30,4650 our results indicate moderate levels of empathy among nursing students at baseline, which had significantly improved, after intervention, as noted by other similar studies 23,41,46,4951…”
Section: Discussionsupporting
confidence: 93%
“… 23 28 30 32 34–38 40 42 47 49 51 52 Thirteen were carried out in the USA and Canada, 29 32–34 40–43 45 46 48 50 seven in Europe, 23 30 36–38 47 51 three in Iran 35 39 49 and one each in Australia, 31 Ghana 28 and China. 52 Fourteen studies provided a definition of empathy. 30 32 34–37 40 43–47 51 52 …”
Section: Resultsmentioning
confidence: 99%
“…Of quantitative programmes deemed as well described, six reported high satisfaction49 51 52 63 69 84 89 while modest and positive but not statistically significant impacts were reported on: pedagogical skills (n=2),38 85 relevance to professional work (n=1),63 resilience and burnout detection/mitigation (n=1)22 70 and confidence/increased sense of personal accomplishment (n=2) 22 38 70. Programmes that reported statistically significant programmatic impacts examined increased empathy (n=3),22 55 70 82 and increased perspective-taking/reflection (n=1) 22 70…”
Section: Resultsmentioning
confidence: 99%
“…During the second screening stage, we read the full texts of records, identifying a further 109 records to exclude due to our discovering on full-text review that they did not meet our established eligibility criteria (figure 1). Following the full-text screening, 61 records qualified for review 15 22 33–89. However, we discovered that several qualifying records addressed identical NM programming efforts at the same institution: that is, 12 records15 22 41 42 44–48 52 70 84 represented 6 programmes.…”
Section: Methodsmentioning
confidence: 99%